Business Management During COVID-19 (International Journal of Innovative Research in Engineering & Management, 2021)
Many firms have closed as a consequence of the COVID-19  outbreak, causing substantial trade disruptions practically in every sector of the global economy. Even though the entire  supply chain has been damaged by the shutdown. Small or Medium Sized Enterprises have been hit the hardest by virus prevention efforts due to their particular characteristics. The  purpose of this study is to investigate how these firms managed with disruptions triggered by closure in term of the employees  or their daily routines to keep their operations running. During  the lockdown in Portugal, a qualitative approach (descriptive or  inductive) was used to achieve this goal, which included  snowball sampling and a questionnaire. It also underlined the  need for government policies to aid small businesses now and  in future. Even though the numeral of businesses observing to  them is strongly determined by the eligibility restrictions or the  speeds with which institution react. The study's main  contribution is to show SMEs' weaknesses, such as a lack of  capital, human resources, digitalization, are the fundamental  hindrance to a meaningful response to the crisis. The  distinctiveness of these contributions is since the managers of  these businesses possess additional talents or qualities, such as  the dynamic capacities to manage a firm in extraordinary crises  or to continue functioning even in the face of a worldwide  blockade. The findings reveal that SMEs confront a slew of  challenges as a result of operational interruptions, which have  resulted in significant liquidity issues, threatening future  continuity and job security.
Keywords: Business; COVID-19; Crisis Management; Pandemic; SMEs